Autism spectrum disorder and 3p24.3p23 triplication: a case report - Martina Siracusano; Maria Stellato; Elisa Carloni; Giulia Miccolo; Assia Riccioni; Romina Moavero; Alessandra Voci; Massimiliano Valeriani; Cinzia Galasso; Adele Pompili; Antonio Pizzuti; Laura Bernardini; et al. (Journal of Medical Case Reports)
Abstract Background The role of copy number variants as genomic mutations causative of neurodevelopmental disorders has been recently established. They can act as risk factors of conditions with multifactorial etiopathogenesis and incomplete penetrance, such as nonsyndromic autism, and, in this case, are often inherited from an unaffected parent. Conversely, dominant syndromes, with high penetrance, can be caused by de novo occurring variants. Case presentation We describe the clinical case, with a detailed characterization of the neuropsychiatric profile, of an almost 3-year-old white (Italian) male child with autism spectrum disorder, developmental delay, mild dysmorphic traits, and congenital anomalies (cardiac septal defects, gliotic changes, thinned corpus callosum, and arachnoid cyst), carrying a 13 Mb de novo 3p24.3p23 triplication. Conclusion Our case suggests that the 3p24 chromosome region could be associated with a syndromic form of autism spectrum disorder and contribute to delineate its distinct clinical features. The extent of the de novo variant described herein is suggestive of pathogenicity, although the genes potentially responsible for the patient’s phenotype are not easy to identify. We hypothesize that the dysregulation of SATB1, already associated to two syndromes (developmental delay with dysmorphic facies and dental anomalies and Den Hoed−De Boer−Voisin syndrome) with a phenotypic spectrum comparable to that of our patient, could be responsible for the clinical phenotype of this case, although the exact pathogenetic mechanism remains to be determined.